Hybridization alters red deer gut microbiome and metabolites - Wei, Limin; Zeng, Bo; Li, Bo; Guo, Wei; Mu, Zhenqiang; Gan, Yunong; Li, Yanhong (Frontiers in Microbiology, 2024)
The host genes play a crucial role in shaping the composition and structure of the gut microbiome. Red deer is listed as an endangered species by the International Union for the Conservation of Nature, and its pilose antlers have good medicinal value.Hybridization can lead to heterosis, resulting in increased pilose antler production and growth performance in hybrid deer. However, the role of the gut microbiome in hybrid deer remains largely unknown. In this study, alpha and beta diversity analysis showed that hybridization altered the composition and structure of the gut microbiome of the offspring, with the composition and structure of the hybrid offspring being more similar to those of of the paternal parents. Interestingly, the LefSe differential analysis showed that there were some significantly enriched gut microbiome in the paternal parents (such as g_Prevotellaceae UCG-003, f_Bacteroidales RF16 group; Ambiguous_taxa, etc.) and the maternal parents (including g_Alistipes, g_Anaerosporobacter, etc.), which remained significantly enriched in the hybrid offspring. Additionally, the hybrid offspring exhibited a significant advantage over the parental strains, particularly in taxa that can produce short-chain fatty acids, such as g_Prevotellaceae UCG-003, g_Roseburia, g_Succinivibrio, and g_Lachnospiraceae UCG-006. Similar to bacterial transmission, metagenomic analysis showed that some signaling pathways related to pilose antler growth ("Wnt signaling pathway", "PI3K Akt signaling pathway", "MAPK signaling pathway") were also enriched in hybrid red deer after hybridization.